Immunological Phenotype and Prognosis of T-Lineage Malignancy in Children - INOUE, Masami; HARA, Junichi; SAKATA, Naoki; TAWA, Akio; KAW-HA, Keisei; ISHIHARA, Shigehiko; OSUGI, Yuko; KOUDERA, Urara; KURAHASHI, Hiroki; YUMURA-YAGI, Keiko; KONISHI, Syouzaburou; SAKO, Masanori (The Japanese Journal of Pediatric Hematology, 1993)
The efficacy of high-dose cytosine arabinoside (HDCA) and phenotypic difference in the prognosis were investigated in T-lineage malignancies (ALL and NHL) in children. Twenty-nine patients from July 1984 to December 1991 were included in this study. Ten patients were treated with the regimen without HDCA (Group A), 9 received single HDCA intensification (Group B) and 10 were treated with cyclic HDCA intensifications (Group C). Disease-free survival (DFS) rates at 48 months were 48%, 38.1% and 71%, respectively. Although these values were not significantly different, cyclic HDCA intensifications seem to be effective for T-ALL and NHL in children, because only 2 patients of Group C relapsed. The phenotype of the samples from Group B and C was divided into 3 groups, i.e., CD3 + group; CD3-, CD4+ and/or CD8+group; and CD3-, CD4-and CD8-group. The patients whose leukemic cells expressed CD3 had a favorable prognosis, and the patients with CD3-, CD4-and CD8-had the worst. Further study is needed to clarify whether the phenotype remains a prognostic factor in patients treated with very intensive therapies or not.